Flexible Bronchoscopy: A Favorable Diagnostic Tool - Rehana, Kausar; Shafiq, Muhammad Mudassir; Hashmi, Fasih (International Journal of Pathology, 2018)
Objective: To determine the diagnostic outcome of fiber-optic bronchoscopic biopsy in Pulmonologydepartment of SZABMU/PIMS Islamabad.Methods: An observational, cross sectional, retrospective study was conducted at Pulmonology department,PIMS Islamabad and record from July 2015 to June 2016 was reviewed. Demographic details of the patients, CTscan, bronchoscopic findings and biopsy outcome and final diagnosis were recorded.Results: Out of 78 study patients, 78.2% were fall between 36 and 75 years of ages and 75.6% were male. 48.7%had right sided and 43.6% had left lung lesion on contrast enhanced CT scan. Right hilar mass (42.1%) and lefthilar mass was (35.3%) was the most common among right and left sided lesions respectively. 50% had rightsided, 39.7% had left sided and 10.3% had randomly distributed findings on bronchoscopy. Upper lobemass/obstruction was the most common finding irrespective of the side of lesion (right 33.3% versus left 29.0%).76.9% of the studied population had cancerous outcome on histopathology and squamous cell carcinoma was themost common final diagnosis (57.4%). Incidence of tuberculosis was very low (n=3). In our study associationbetween smoking, gender and age with final diagnosis was not significant.Conclusion: Diagnostic yield of flexible bronchoscopy is good enough, very useful for the diagnosis ofpulmonary lesions and safe as a day care procedure.